Local Emissions Drive Summer PM2.5 Pollution Under Adverse Meteorological Conditions: A Quantitative Case Study in Suzhou, Yangtze River Delta - Minyan Wu; Ningning Cai; Jiong Fang; Ling Huang; Xurong Shi; Yezheng Wu; Li Li; Hongbing Qin (Atmosphere)
Accurately identifying the sources of fine particulate matter (PM2.5) pollution is crucial for pollution control and public health protection. Taking the PM2.5 pollution event that occurred in Suzhou in June 2023 as a typical case, this study analyzed the characteristics and components of PM2.5, and quantified the contributions of meteorological conditions, regional transport, and local emissions to the summertime PM2.5 surge in a typical Yangtze River Delta (YRD) city. Chemical composition analysis highlighted a sharp increase in nitrate ions (NO3−, contributing up to 49% during peak pollution), with calcium ion (Ca2+) and sulfate ion (SO42−) concentrations rising to 2 times and 7.5 times those of clean periods, respectively. Results from the random forest model demonstrated that emission sources (74%) dominated this pollution episode, significantly surpassing the meteorological contribution (26%). The Weather Research and Forecasting model combined with the Community Multiscale Air Quality model (WRF–CMAQ) further revealed that local emissions contributed the most to PM2.5 concentrations in Suzhou (46.3%), while external transport primarily originated from upwind cities such as Shanghai and Jiaxing. The findings indicate synergistic effects from dust sources, industrial emissions, and mobile sources. Validation using electricity consumption and key enterprise emission data confirmed that intensive local industrial activities exacerbated PM2.5 accumulation. Recommendations include strengthening regulations on local industrial and mobile source emissions, and enhancing regional joint prevention and control mechanisms to mitigate cross-boundary transport impacts.